First record of young-of-the-year Scalloped hammerhead shark, Sphyrna lewini (Carcharhiniformes: Sphyrnidae) from Isla del Coco National Park, Costa Rica - Zanella, Ilena; López-Garro, Andrés; McComb-Kobza, D. Michelle; Golfín-Duarte, Geiner; Pérez-Montero, Maikel; Morales, Josué (Revista de Biología Tropical, 2016)
The Scalloped hammerhead shark, Sphyrna lewini is a coastal and pelagic circumglobal species that resides within coastal warm temperate and tropical seas. Sphyrna lewini exhibits strong intraspecific segregation: neonates and young-of-the-year spend the first part of life in coastal inshore waters (nursery grounds), while adults migrate offshore, returning to protected nursery habitats for mating and pupping. On December 3, 2014, at approximately 19:00 hr, four young-of-the-year S. lewini were caught with hand line in Wafer Bay, Isla del Coco, Costa Rica (5°32’42.4” N - 87°03’45.3” W). A total of three males (total length (TL): 73, 73, 76 cm) and one female (TL: 75 cm) were recorded. The presence of these individuals at Isla del Coco suggests that a pregnant female gave birth in or near Wafer Bay, which may be a nursery ground for S. lewini. We recommend further study to evaluate the presence and movements of young-of-the-year and juvenile S. lewini in Wafer Bay to determine if this was an isolated incident or if the bay is a nursery ground for S. lewini.